2019
DOI: 10.33105/itrev.v4i3.144
|View full text |Cite
|
Sign up to set email alerts
|

Kesinambungan fiskal dan estimasi fiscal reaction function Indonesia tahun 1977-2017

Abstract: This study aims to identify whether Indonesian fiscal condition in 1977–2017 is sustainable as measured by the government responses to debt burden. Studi on fiscal sustainability is very important since failing to identify its occurrence and determinants will detrimental to fiscal and macroeconomic policy. This study uses Auto-Regressive Distributed Lag – Error Correction Mechanism (ARDL-ECM) to estimate short-term and long-term fiscal reaction functions. The result shows that in the long-term the government r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Among the seven European countries in the sample (France, Germany, Ireland, Portugal, Spain, Italy, and Greece), only Italy and Greece's fiscal policies were sustainable. Similarly, Kurniawan (2015) and Solikin and Choirunnisah (2019) found a positive relationship between primary balance and debt in Indonesia. In Japan's case, it was indicated that the primary balance did not respond to the debt ratio increase (Doi et al, 2011).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Among the seven European countries in the sample (France, Germany, Ireland, Portugal, Spain, Italy, and Greece), only Italy and Greece's fiscal policies were sustainable. Similarly, Kurniawan (2015) and Solikin and Choirunnisah (2019) found a positive relationship between primary balance and debt in Indonesia. In Japan's case, it was indicated that the primary balance did not respond to the debt ratio increase (Doi et al, 2011).…”
Section: Introductionmentioning
confidence: 89%
“…In particular, Germany, the Netherlands, Finland, Austria, and the UK have the most unsustainable policy problems. Kurniawan (2015) and Solikin and Choirunnisah (2019) examines the sustainability of Indonesia fiscal policy and found a positive relationship between primary balance and debt in Indonesia. Baharumshah et al (2017) analyze the sustainability of Malaysia's fiscal policy during 1980-2014.…”
Section: Hypothesis Development the Relationship Between Debt And Primary Balancementioning
confidence: 99%
See 1 more Smart Citation
“…To maintain a stable economic momentum, the government strives to achieve fiscal sustainability through the APBN instrument so that government expenditure can be maintained in a safe condition and sufficient for public service needs in the medium and long-term framework (Solikin & Choirunnisah, 2019).…”
Section: A Review Of Expenditures and Electricity Subsidies Policy In...mentioning
confidence: 99%
“…Pada kondisi keuangan yang sehat, pemerintah daerah memiliki peluang yang lebih besar untuk memperoleh pinjaman dari kreditur. Dengan demikian, pemerintah daerah tidak akan menghadapi risiko krisis yang lebih besar dan tetap mampu melakukan pengeluaran untuk pemenuhan kebutuhan publik yang optimal (Solikin & Choirunnisah, 2019). Pengeluaran pemerintah yang lebih tinggi mendorong pertumbuhan ekonomi regional sehingga potensi perpajakan daerah akan meningkat.…”
Section: Tinjauan Pustakaunclassified